24-week, all-oral regimens for pulmonary rifampicin-resistant tuberculosis in TB-PRACTECAL trial sites: an economic evaluation - Sweeney, Sedona; Laurence, Yoko V; Berry, Catherine; Singh, Maninder Pal; Dodd, Matthew; Fielding, Katherine; Kazounis, Emil; Moodliar, Ronelle; Solodovnikova, Varvara; Tigay, Zinaida; Liverko, Irina; Parpieva, Nargiza; et al. (The Lancet global health, 2025)
New 6-month rifampicin-resistant tuberculosis treatment regimens containing bedaquiline, pretomanid, and linezolid (BPaL) with or without moxifloxacin or clofazimine, could improve treatment efficacy, safety, and tolerability, and free up resources within the health system. Following a change to WHO rifampicin-resistant tuberculosis treatment guidelines, countries are facing difficult decisions about when and how to incorporate new drug regimens into national guidelines. We aimed to assess the probability of BPaL-based regimens being cost-saving using data collected in the TB-PRACTECAL trial. This economic evaluation using a cost-utility analysis was embedded in five TB-PRACTECAL trial sites in Belarus, Uzbekistan, and South Africa. Between Nov 19, 2020, and Sept 27, 2022, we collected detailed primary unit cost data in six hospitals and four ambulatory health facilities and collected data on patient-incurred costs from 73 trial participants. The primary efficacy endpoint of the main trial, a composite of unfavourable outcomes (death, disease recurrence, treatment failure, early discontinuation of therapy, withdrawal, or loss to follow-up) and clinically important safety outcomes by 72 weeks of follow-up were incorporated into the analysis. Societal perspective cost data and effect outcome data were input into a Markov model to estimate the cost per disability-adjusted life-year (DALY) averted by BPaL-based regimens compared with the standard of care over a 20-year time horizon. We conducted a range of univariate and probabilistic sensitivity analyses to test our findings. BPaL-based regimens averted a mean of 1·28 DALYs and saved a mean of US$14 868 (SD 291) per person from the provider perspective compared with standard-of-care regimens over 20 years. Patient-incurred costs were reduced by a mean of $172 (SD 0·84) in BPaL-based regimen groups compared with standard of care. The main cost drivers for both providers and patients were inpatient bed-days; the duration of the inpatient period varied across countries. Varying a range of model parameters affected the degree of cost savings but did not change the finding that BPaL-based regimens are cost-saving compared with standard of care. This trial-based evidence adds to consistent indications from modelling studies that BPaL-based regimens are cost-saving for both the patient and health system. Urgent implementation of BPaL-based regimens in countries with a high burden of tuberculosis could improve treatment of rifampicin-resistant tuberculosis, reduce pill burden, and free up desperately needed resources within the health system. Médecins Sans Frontières.